Legal liability: seven doctrinal approaches to understanding its essence - V. H. Zhornokui (Law and Safety)
The article provides a critical analysis of the civil law doctrine of understanding the “legal liability” category. Seven main approaches to the interpretation of the category under study are identified and their advantages and disadvantages are highlighted. The author concludes that neither current legislation nor legal doctrine is consistent on the issue under study.